2006
DOI: 10.1086/506565
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cryptosporidiosis Is Associated with a Persistent Systemic Inflammatory Response

Abstract: Cryptosporidiosis in young children prompts local inflammation in the intestinal tract. We studied a cohort of young children with cryptosporidiosis to determine whether systemic inflammatory responses occur and, if so, to evaluate whether inflammation persists after infection. Cryptosporidiosis was associated with increased levels of interleukin-8 and tumor necrosis factor- alpha systemically, which persisted at 6 months after enrollment. The level of intestinal tumor necrosis factor- alpha was elevated at en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…This is in agreement with an earlier study (14) which reported higher levels of IL-10 and IFN-␥ in HIV-seronegative patients with a history of cryptosporidiosis but comparatively low levels of IL-10 and no production of IFN-␥ in healthy individuals. In contrast, other reports have failed to detect IFN-␥ in cryptosporidiosis patients' PBMCs in response to Cryptosporidium (19,20). In the present study, no significant difference was observed in the cytokine responses to Cryptosporidium between immunosuppressed and immunocompetent individuals infected with Cryptosporidium.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with an earlier study (14) which reported higher levels of IL-10 and IFN-␥ in HIV-seronegative patients with a history of cryptosporidiosis but comparatively low levels of IL-10 and no production of IFN-␥ in healthy individuals. In contrast, other reports have failed to detect IFN-␥ in cryptosporidiosis patients' PBMCs in response to Cryptosporidium (19,20). In the present study, no significant difference was observed in the cytokine responses to Cryptosporidium between immunosuppressed and immunocompetent individuals infected with Cryptosporidium.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we identified IFN-␥ in the intestines of a minority of volunteers only after Cryptosporidium challenge, and IFN-␥ expression was limited to the volunteers who appeared to be immune (that is, either seropositive or resistant to a challenge with a dose that was greater than the dose that would infect most volunteers) (93). Other groups failed to detect IFN-␥ in stools or stimulated PBMC obtained at the time of acute infection (29,44,45). Thus, while IFN-␥ seems to be critical for the memory response, other mechanisms may play a larger role in resolution of acute infection.…”
Section: Ifn-␥-dependent Immune Response and Cytokinesmentioning
confidence: 89%
“…Similarly, increased CXCL-8 levels were found in the stools of Cryptosporidium-infected Haitian children compared to controls (44,45). Also, peripheral blood mononuclear cells (PBMC) of infected Haitian children expressed higher levels of CXCL-8 when they were restimulated in vitro up to 6 months after infection (45). In a study of Brazilian children, more stool samples containing elevated levels of IL-8 came from control children than from infected children (3).…”
Section: Chemokinesmentioning
confidence: 99%
See 2 more Smart Citations